1995
DOI: 10.1021/bi00043a002
|View full text |Cite
|
Sign up to set email alerts
|

Extensive nonrandom structure in reduced and unfolded bovine pancreatic trypsin inhibitor

Abstract: Two-dimensional 1H NMR spectra of an analog of reduced BPTI at pH 4.5, 1 degrees C, have been assigned. Spectra indicate considerable conformational averaging, as expected for a flexible, unfolded protein. The presence of extensive nonrandom structure is detected by the presence of NHi-NHi + 1 and aromatic-aliphatic NOEs. Sequential amide-amide NOEs indicate that turn-like conformations are significantly populated at 18 pairs of residues along the chain. Many of these are located in a turn, loop, or helix in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 25 publications
(46 reference statements)
6
52
0
Order By: Relevance
“…The farultraviolet CD spectrum of the reduced protein is very similar to those seen for other unfolded proteins and indicates an absence of regular secondary structure~Kosen et al, 1981!. On the other hand, NMR studies of reduced BPTI and peptide fragments thereof have demonstrated the presence of numerous specific, but probably transient, interactions, and local conformational preferences Lumb & Kim, 1994;Pan et al, 1995!. Interestingly, many of the interactions detected by NMR are not present in the native protein, and it has been suggested that forming any of the three native disulfides causes the disruption of these non-native interactions~Pan et al, 1995!.…”
Section: The Nature and Role Of Nonrandom Structure In Fully Reduced mentioning
confidence: 55%
“…The farultraviolet CD spectrum of the reduced protein is very similar to those seen for other unfolded proteins and indicates an absence of regular secondary structure~Kosen et al, 1981!. On the other hand, NMR studies of reduced BPTI and peptide fragments thereof have demonstrated the presence of numerous specific, but probably transient, interactions, and local conformational preferences Lumb & Kim, 1994;Pan et al, 1995!. Interestingly, many of the interactions detected by NMR are not present in the native protein, and it has been suggested that forming any of the three native disulfides causes the disruption of these non-native interactions~Pan et al, 1995!.…”
Section: The Nature and Role Of Nonrandom Structure In Fully Reduced mentioning
confidence: 55%
“…Our results show that the denatured ensemble of BPTI is not a fully random coil but collapsed with some ordered structure. 69,70 There are several interesting differences among the denatured states. Unfolded reduced BPTI with all three disulfide bonds broken sample non-native conformations that are absent in the unfolded 14 -38 BPTI analogues.…”
Section: Denatured Ensemblementioning
confidence: 99%
“…It is only recently that structural information for the denatured state has become available at atomic resolution because of developments in high field NMR spectroscopy (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). These studies have focused on areas of persistent structure, with the aim of obtaining insight into the relationship between sequence, structure, and in particular, the mechanism of folding.…”
Section: Introductionmentioning
confidence: 99%